2022
DOI: 10.1101/2022.02.16.480700
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dual-Drug Loaded Biomimetic Chitosan-Collagen Hybrid Nanocomposite Scaffolds for Ameliorating Potential Tissue Regeneration in Diabetic Wounds

Abstract: Diabetes Mellitus (DM) is one of the most concerning conditions, and its chronic complications are nearly synonymous with inflammation, oxidative stress, and infections. In the acute inflammatory phase of diabetic wound healing (DWH), reducing excessive reactive oxygen species (ROS) and inflammatory response of the wound is a necessary treatment. The current work used a mix of emulsification and lyophilization approaches to investigate the effects of resveratrol microparticles (RES-GMS) loaded chitosan-collage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…The antimicrobial activity obtained against S. aureus and, respectively, against S. aureus MRSA is in accordance with the results obtained by other scientists [30][31][32][33]51,52], who obtained significant antimicrobial activity for S. aureus, S. aureus MRSA, and P. aeruginosa only in the case of composite biofilms which contain collagen, chitosan, and silver. Regarding the action mechanism for biomaterial composites with chitosan and clotrimazole, in the case of S. aureus or S. aureus MRSA, most probably chitosan binds to teichoic acids, increases membrane permeability, and causes membrane depolarization [53], acting synergically with clotrimazole.…”
Section: Antimicrobial Activitysupporting
confidence: 90%
See 1 more Smart Citation
“…The antimicrobial activity obtained against S. aureus and, respectively, against S. aureus MRSA is in accordance with the results obtained by other scientists [30][31][32][33]51,52], who obtained significant antimicrobial activity for S. aureus, S. aureus MRSA, and P. aeruginosa only in the case of composite biofilms which contain collagen, chitosan, and silver. Regarding the action mechanism for biomaterial composites with chitosan and clotrimazole, in the case of S. aureus or S. aureus MRSA, most probably chitosan binds to teichoic acids, increases membrane permeability, and causes membrane depolarization [53], acting synergically with clotrimazole.…”
Section: Antimicrobial Activitysupporting
confidence: 90%
“…The composite biomaterials based on collagen, chitosan, resveratrol, and doxycycline obtained by Tallapaneni and collaborators, for use in healing the wounds of diabetic patients, inhibit the development of pathogenic microorganisms, such as S. aureus, S. aureus MRSA, P. aeruginosa, and E. coli, (inhibition diameters obtained were more than 4 cm). Cytotoxicity tests performed with composite biomaterial concentrations in the culture medium of (31 ÷ 250) µg/mL), on Balb/3T3 murine fibroblast cell lines showed that, after 72 h, the cell viability was under 70% [33].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels engineered from polysaccharides through ionic and chemical means demonstrated high cell viability, cell binding affinity, and proliferation in wound healing applications, such as wound dressings and matrices for tissue repair and regeneration [ 107 ]. Chitosan-collagen cross-linked scaffolds also showed optimal porosity, reduced matrix degradation, and prolonged drug release with acceptable biocompatibility, enhanced cell development, and a prolonged release [ 108 ]. Chitosan can also be integrated with pectin and dextrin.…”
Section: D Printed Drug Loaded Nanomaterials For Wound Healingmentioning
confidence: 99%
“… 3D Scaffold Product Description Evaluation Outcomes Reference Chitin-covered CeNPs Cerium NP-based wound dressing hydrogels covered by chitin an efficient fluid handling capacity and antimicrobial activity [ 111 ]. RES-DOX–CS–CLG Cross-linked scaffold emulsification and lyophilization based formulations of resveratrol microparticles (RES-GMS) loaded chitosan-collagen (CS-CLG) scaffold with doxycycline (DOX) on DWH optimal porosity, reduced matrix degradation, and prolonged drug release [ 108 ] promoted cell proliferation in the dermis by improving fibroblast function CS-Pec-Dex Wound patch propolis extract with beta cyclodextrin embedded with chitosan on pectin 3D-printed films using SSE. good in vitro antimicrobial activities [ 109 ] accelerated wound-healing effect PhycoTrix™ bioink a dual-network polysaccharide hydrogel 3D printed scaffold engineered through ionic and chemical means high cell viability, cell binding affinity, and proliferation compared to alginate studies [ 107 ] promising application as wound dressings and matrices for tissue repair and regeneration Gentamycin Polyelectrolyte Multilayers Conformal, consistent, inkjet printed coatings on a cotton substrate loaded with the antibiotic gentamicin.…”
Section: D Printed Drug Loaded Nanomaterials For Wound Healingmentioning
confidence: 99%
“…After 24 h, the cells treated with the scaffold migrated much quicker than the control samples. 19 Ren et al fabricated anti-inflammatory and antibacterial Ag@hesperidin core–shell nanoparticles embedded in nanofibers for the treatment of an infected wound. These nanoparticles presented effective antibacterial properties against E. coli and S. aureus .…”
Section: Introductionmentioning
confidence: 99%